Perancangan UI/UX Aplikasi E-Commerce Berbasis Website Pada Toko Cv. Intan Jaya Gemilang Dengan Menggunakan Lean User Experience - Muhamad Riski, Muhamad Riski; Sofalina, Fresa Dwi Juniar (Buletin Ilmiah Informatika Teknologi, 2024)
CV Shop. Intan Jaya Gumilanh is a shop that sells various accessories that was founded in 2020. This shop provides various accessories such as graduation sashes, certificates, graduation dolls. Problems that occurred at the CV shop. Intan Jaya Gumilang is that customers can only make transactions and view catalogs when they come to the shop and shop employees also experience difficulties in recording sales and calculating shop turnover because at the CV shop. Intan Jaya Gemilang still uses books and a calculator in its transaction process, resulting in frequent differences in the number of goods calculated. The increasingly rapid development of information technology and the increasing number of users of information systems require companies or agencies to prioritize more effective and efficient information services. As one solution to the problem above, the solution is designing the UI/UX of a web-based e-commerce application using the Lean UX method because this method has the advantage of a fast success rate but also remains focused on the level of understanding of the product experience that will be created